2021
DOI: 10.11591/ijere.v10i4.21518
|View full text |Cite
|
Sign up to set email alerts
|

Managing educational institutions: School heads’ leadership practices and teachers’ performance

Abstract: School heads are agents of change who contribute a major impression on the educational milieu through their information-sharing methods, creating supportive social connections, participating in mentoring programs, and fostering progress. Hence, this study ascertained the interrelation between the public school head’s leadership practices and teachers’ performance. As correlation research, simple random sampling was used to calculate the sample size for teachers, while total enumeration was used for school head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Various research results have shown that the leadership behavior of principals plays a key role in preparing qualified teachers [9], [10]. Transformational principals can serve as important agents to create a school vision, assist teachers in increasing their confidence, promote quality teaching practices, and assist teachers in developing teacher competencies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Various research results have shown that the leadership behavior of principals plays a key role in preparing qualified teachers [9], [10]. Transformational principals can serve as important agents to create a school vision, assist teachers in increasing their confidence, promote quality teaching practices, and assist teachers in developing teacher competencies [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of migration towards a teaching based on the use of technological tools, it is perceived in many cases that teachers have a poor use of technologies or virtual tools [12]- [14]; and it is that the teacher must have the capacity for adaptability and flexibility to the evolving environments of teaching that are being developed these days [15]- [17]; whose lack or lack influences the university educational quality, becoming a relevant and necessary aspect to permanently evaluate the teaching performance in various factors, with the purpose of implementing a quality education [18], [19]. In recent years, university educational institutions have carried out a poor systematization of teacher performance evaluation processes, so it is important to incorporate mechanisms that contribute to its assessment [20]; consistent with the evolution of data processing strategies [21], [22]; making these institutions more significant and even more effective [23].…”
Section: Introductionmentioning
confidence: 99%
“…Other elements that affect teachers' performance effectiveness in the organisational life are principal leadership, work environment and trust in leadership. The principal leadership style has an effect on the performance of the teacher (Abu Nasra & Arar, 2020, Aquino et al, 2021, Mislia et al, 2021, Parveen et al, 2022. Work environment affects the performance of a teacher (Ivanova & Suvorova, 2022).…”
Section: Introductionmentioning
confidence: 99%